Chemical characterization of Eucalyptus (Eucalyptus globulus) leaf essential oil and evaluation of its antifungal, antibacterial and antioxidant activities: Biological activities of Eucalyptus essential oil - Haj Moussa, Hakim; Sara, Benamara; Benhalima, Hadia; Benaliouche, Fouzia; Sbartai, Ibtissem; Sbartai, Hana (Cellular and Molecular Biology, 2025)
This study investigates the chemical composition of the essential oil (EO) extracted by hydrodistillation from dry Eucalyptus leaves (Eucalyptus globulus) and its antifungal, antibacterial and antioxidant potential. The Eucalyptus leaves were harvested in the commune of Seraïdi (north-eastern Algeria). Chemical analysis carried out by chromatography coupled with mass spectrophotometry (GC-SM) revealed the presence of 20 molecules representing approximately 100% of the overall component, with a yield of 1.58%. This oil is composed mainly of linalool (30.09%), followed by b-Linalyl oxide (13.93%), Camphor (12.09%), 1,8-Cineole=eucalyptol (10.95%) and Bergamol (10.03%). Other constituents were identified at relatively medium (Epoxylinalol - 8.82%, Borneol - 5.71%) and low (alpha-Terpinol - 1.11) levels. This result shows that this EO differs from those usually extracted from eucalyptus leaves because it is of linalool chemotype and not eucalyptol. The determination of the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) was carried out to evaluate the antifungal activity of Eucalyptus EO on the growth of Fusarium roseum mycelium. The values recorded are 2500µg/ml for the MIC and 4000µg/ml for the MFC. The results obtained revealed an antifungal activity of this oil for practically all doses applied against Fusarium mycelial proliferation despite the low reported levels of 1,8-cineole compared to the other components. The antibacterial activity against the Pseudomonas savastanoi strain was also examined which revealed effectiveness of this oil. In parallel, the DPPH test revealed a moderate antioxidant activity of the studied EO compared to Vit C with an IC50 17mg/ml probably due to its components’ antagonistic or synergistic effect.